2021
DOI: 10.1155/2021/8898919
|View full text |Cite
|
Sign up to set email alerts
|

Green Tea (Camellia sinensis) Extract Increased Topoisomerase IIβ, Improved Antioxidant Defense, and Attenuated Cardiac Remodeling in an Acute Doxorubicin Toxicity Model

Abstract: Experimental studies have shown the action of green tea in modulating cardiac remodeling. However, the effects of green tea on the cardiac remodeling process induced by doxorubicin (DOX) are not known. Therefore, this study is aimed at evaluating whether green tea extract could attenuate DOX-induced cardiac remodeling, assessed by cardiac morphological and functional changes and associated with the evaluation of different modulators of cardiac remodeling. The animals were divided into four groups: the control … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 37 publications
1
8
0
Order By: Relevance
“…Xiang et al (2016) reported the suppressive effects of Camellia sinensis on breast cancer. Camellia sinensis extract was reported to attenuate cardiac remodeling accompanied by acute doxorubicin toxicity (Modesto et al, 2021) and suppress brain ischemic injury induced by middle cerebral artery occlusion (Machin et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…Xiang et al (2016) reported the suppressive effects of Camellia sinensis on breast cancer. Camellia sinensis extract was reported to attenuate cardiac remodeling accompanied by acute doxorubicin toxicity (Modesto et al, 2021) and suppress brain ischemic injury induced by middle cerebral artery occlusion (Machin et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…Likewise, pretreatment with a green tea extract administered before regional myocardial ischemia-reperfusion improved myocardial contractility through the attenuation of calcium overload in rats [ 45 ]. The beneficial effects of tea on cardiac function are the result, at least in part, of the presence of polyphenols which are reported to exert antioxidant effects in the heart both in vivo [ 46 , 47 ] and in vitro [ 48 , 49 , 50 ]. However, in this study we did not find differences in the gene expression of antioxidant enzymes among the experimental groups.…”
Section: Discussionmentioning
confidence: 99%
“…MDA, a major metabolite of oxidative free radicals, reflects the degree of peroxidation of myocardial tissue. And SOD as a vital antioxidant enzyme can improve myocardial oxidative stress injury by scavenging oxygen free radicals [ 6 , 37 ]. AEBA significantly decreased the content of MDA and increased the serum SOD activity, which might contribute to its effects on alleviating the injury degree of inflammation and fibrosis of the heart tissue in ISO-induced MI rats.…”
Section: Discussionmentioning
confidence: 99%
“…It is well recognized that oxidative stress, caused by the imbalance between the scavenging and production of oxygen radicals, aggravates maladaptive left ventricular remodeling [ 5 ]. Superoxide dismutase (SOD), an important antioxidant enzyme, is decreased in MI [ 6 ]. Additionally, oxidative stress is associated with inflammatory responses in the infarcted heart, manifested by the infiltration of inflammatory cells (such as macrophages), secretion of proinflammatory mediators [ 7 ], and activation of the inflammatory cascades [ 8 ], resulting in exacerbating abnormal vascular remodeling and cardiac dysfunction [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%